2016
DOI: 10.1111/iju.13174
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term prospective study of the persistence of solifenacin succinate in previously untreated Japanese female patients with overactive bladder

Abstract: Approximately one-quarter of previously untreated Japanese overactive bladder female patients continue solifenacin treatment for 3 years. Many patients discontinue solifenacin for various reasons, including symptom resolution and adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…13,14 Previous studies, each from a single healthcare site, have investigated persistence with OAB medications in the Japanese patient population, and recent investigations have shown that 12-month persistence rates with mirabegron vary between 12% and 29%. [15][16][17][18] Building on these results, the present study is the first large-scale, nationwide survey in Japan to explore persistence and adherence to mirabegron and antimuscarinics using data from two databases.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Previous studies, each from a single healthcare site, have investigated persistence with OAB medications in the Japanese patient population, and recent investigations have shown that 12-month persistence rates with mirabegron vary between 12% and 29%. [15][16][17][18] Building on these results, the present study is the first large-scale, nationwide survey in Japan to explore persistence and adherence to mirabegron and antimuscarinics using data from two databases.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, oral antimuscarinic agents have been the mainstay of OAB therapy, although the associated side‐effects (including dry mouth and constipation) further affect quality of life and adversely affect treatment adherence . Treatment persistence of OAB medication is lower than for any other chronic disease therapy, with a number of studies demonstrating poor treatment persistence with antimuscarinics . As such, OAB treatments with alternative mechanisms of action and improved tolerability are desirable.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Treatment persistence of OAB medication is lower than for any other chronic disease therapy, 6 with a number of studies demonstrating poor treatment persistence with antimuscarinics. [7][8][9][10][11][12][13][14][15][16][17][18] As such, OAB treatments with alternative mechanisms of action and improved tolerability are desirable.…”
Section: Introductionmentioning
confidence: 99%
“…The resolution of bothering symptoms has been given as one of the most common reasons for termination of treatment and may be achieved in more than one-third of OAB cases. [11][12][13][14][15] Other common reasons for medication discontinuation are adverse effects and/or failure of expected clinical outcome. There is no consensus regarding the optimal duration of OAB treatment as, in the vast majority of available clinical trials, time periods of drug administration have been reported to range from 2 weeks to 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study from Japan (n=73), assessing persistence rates of solifenacin 5 mg daily treatment during a 3-year period, demonstrated that 25% of patients required retreatment at an average 10 months after termination. 12 Until now, there is paucity of data on the impact of physiotherapy on OAB recurrence after treatment cessation. Further research in this area is warranted as behavioral therapies, including pelvic floor muscle exercises, are relatively non-invasive and could benefit patient health overall.…”
Section: Cuaj -Original Researchmentioning
confidence: 99%